First Branchial Cleft Anomalies: Managing Various Cervico-Facial Anomalies and Otologic Malformations at a large Canadian Referral Centre - Joshua Gurberg; John Paul Moxham; Jeffrey P Ludemann (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Background: Branchial cleft anomalies account for approximately 17% of pediatric neck masses and 30% of all congenital neck lesions; of these, less than 1% involve the first branchial cleft. We report several novel otologic malformations encountered in children with first branchial cleft anomalies; as well as our surgical techniques and outcomes.  Methods: We conducted a retrospective chart review of all patients consecutively referred to the senior authors at a tertiary-care Pediatric Otolaryngology clinic for first branchial cleft anomalies over a 14-year period. Patients underwent computerized tomography scan with contrast, otoscopy plus tympanic microsurgery, when indicated (29%), methylene blue mapping of the cutaneous opening, when present (57%), intra-operative facial nerve monitoring, and anterograde or retrograde facial nerve dissection, when necessary (86%).  Results: Seven patients presented with fi rst branchial cleft anomalies, at an average age of 3.9 years. Five of seven patients (71%) presented with cervico-facial infection. Four of the anomalies were sinuses, 2 were cysts and 1 was a fistula. Two patients had a classic myringeal web. One patient had a large posterior intratympanic keratoma, partial myringeal duplication, and wax-pocket; while another patient had external auditory canal triplication and a small intratympanic keratoma. In 6 cases (86%) there was distortion of anatomical landmarks and retrograde facial nerve dissection was therefore employed. In one patient, no branches of the facial nerve were identified during excision. In two patients, re-anastomosis of a small distal branch of the facial nerve was performed. Five patients (71%) experienced transient facial nerve weakness. However, with a mean length of follow-up of 7.5 years, no permanent facial nerve weakness, recurrence, or hearing loss has been identified.  Conclusions: We present several novel otologic fi rst branchial cleft fi ndings, as well as the experience of a two-surgeon team using methylene blue mapping plus monitored and primarily retrograde facial nerve dissection. This approach appears relatively safe and effective in children with these highly variable anomalies.